2015
DOI: 10.4239/wjd.v6.i2.358
|View full text |Cite
|
Sign up to set email alerts
|

Association of gene variants with susceptibility to type 2 diabetes among Omanis

Abstract: Results confirmed the association of KCNJ11 (rs5219), TCF7L2 (rs7903146), CDKAL1 (rs10946398) and CDKN2A/B (rs10811661) gene variants with susceptibility to T2D among Omani Arabs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 58 publications
3
23
1
Order By: Relevance
“…A recent study by Kamura et al [25] suggested that the association between FTO variants and T2D is mediated through the lifetime maximum BMI at the time of or before diagnosis of T2D. Nevertheless, our lack of association with the T2D risk has also been reported in populations of similar genetic background to the Kuwaiti population [26, 27]. It is apparent that ethnicity plays a role in FTO rs9939609 and T2D risk among different populations, possibly under the influence of other T2D susceptibility factors of stronger effect.…”
Section: Discussioncontrasting
confidence: 49%
“…A recent study by Kamura et al [25] suggested that the association between FTO variants and T2D is mediated through the lifetime maximum BMI at the time of or before diagnosis of T2D. Nevertheless, our lack of association with the T2D risk has also been reported in populations of similar genetic background to the Kuwaiti population [26, 27]. It is apparent that ethnicity plays a role in FTO rs9939609 and T2D risk among different populations, possibly under the influence of other T2D susceptibility factors of stronger effect.…”
Section: Discussioncontrasting
confidence: 49%
“…However, the association between FTO variants and T2DM was controversial. Consistent with two previous case-control studies [25,26], we found no significant association of FTO variants with T2DM. Also, we did not observe any possible haplotype associated with T2DM in the strong linkage disequilibrium region (block 1).…”
Section: Discussionsupporting
confidence: 92%
“…It was the first T2D susceptibility gene identified in linkage studies (HORIKAWA et al 2000), with multiple subsequent GWAS or candidate gene studies having also identified an association between variants near CAPN10 and T2D risk and other diabetes-related phenotypes (BAIER et al 2000;EVANS et al 2001;OROZCO et al 2014;IBRAHIM et al 2015;CUI et al 2016;ZHAO et al 2016;BAYRAMCI et al 2017;HOU et al 2017;CASTRO-MARTINEZ et al 2018). However, many other studies failed to replicate these findings (HEGELE et al 2001;TSAI et al 2001;KHAN et al 2014;AL-SINANI et al 2015;PLENGVIDHYA et al 2015;ZHANG et al 2019). It is tempting to speculate that one potential reason for the inconsistent results could be an incomplete understanding of epistatic interactions between CAPN10 and other loci.…”
Section: Among the Most Significant Genes Whose Expression Is Regulatmentioning
confidence: 99%